Epitaxial Growth of 1D Atomic Chain Based Se Nanoplates on Monolayer ReS2 for High‐Performance Photodetectors. (10th October 2018) - Qin, Jing‐Kai; Qiu, Gang; He, Wen; Jian, Jie; Si, Meng‐Wei; Duan, Yu‐Qin; Charnas, Adam; Zemlyanov, Dmitry Y.; Wang, Hai‐Yan; Shao, Wen‐Zhu; Zhen, Liang; Xu, Cheng‐Yan; et al.
Abstract: Mixed‐dimensional (0D, 1D, and 3D) heterostructures based on 2D layered materials have been proven as a promising candidate for future nanoelectronics and optoelectronics applications. In this work, it is demonstrated that 1D atomic chain based Se nanoplates (NPs) can be epitaxially grown on monolayer ReS2 by a chemical transport reaction, thereby creating an interesting mixed‐dimensional Se/ReS2 heterostructure. A unique epitaxial relationship is observed with the (110) planes of the Se NPs parallel to the corresponding ReS2 (010) planes. Experimental and theoretical studies reveal that the Se NPs could conjugate with underlying monolayer ReS2 via strong chemical hybridization at heterointerface, which is expected to originate from the intrinsic defects of ReS2 . Remarkably, photodetectors based on Se/ReS2 heterostructures exhibit ultrahigh detectivity of up to 8 × 10 12 Jones, and also show a fast response time of less than 10 ms. These results illustrate the great advantage of directly integrated 1D Se based nanostructure on planar semiconducting ReS2 films for optoelectronic applications. It opens up a feasible way to obtain mixed‐dimensional heterostructures with atomic interfacial contact by epitaxial growth. Abstract : 1D atomic chain based Se nanoplates (NPs) are epitaxially grown on monolayer ReS2 to form an interesting mixed‐dimensional Se/ReS2 heterostructure. Experimental and theoretical studies reveal that the Se NPs are chemically hybridized with underlying monolayer ReS2 through intrinsic defects in ReS2 . Photodetectors based on Se/ReS2 heterostructures exhibit ultrahigh detectivity and fast response time.